L445P mutation on heavy chain stabilizes IgG4 under acidic conditions. Issue 7 (3rd October 2019) - Xu, Chang-Ai; Feng, Andrew Z.; Ramineni, Charan K.; Wallace, Matthew R.; Culyba, Elizabeth K.; Guay, Kevin P.; Mehta, Kinjal; Mabry, Robert; Farrand, Stephen; Xu, Jin; Feng, Jianwen
ABSTRACT: IgG4, a common type of therapeutic antibody, is less stable during manufacturing processes compared with IgG1 . Aggregation and fragmentation are the two main challenges. Here, we report instability of the heavy chain (HC) C-terminal region under acidic conditions, which leads to cleavage and aggregation. Leu 445, at the C-terminal region of the HC in IgG4, plays a critical role in its acid-induced fragmentation and subsequent aggregation. We found that mutating HC C-terminal Leu 445 to Pro (the corresponding residue in IgG1 ) in IgG4 _CDR-X significantly reduces fragmentation and aggregation, while mutating Pro 445 to Leu in IgG1 _CDR-X promotes fragmentation and aggregation. HC C-terminal Gly 446 cleavage was observed in low pH citrate buffer and resulted in further fragmentation and aggregation, whereas, glycine buffer can completely inhibit the cleavage and aggregation. It is proposed that cleavages occur through acid-induced hydrolysis under acidic conditions and glycine stabilizes IgG4 via two main mechanisms: 1) product feedback inhibition of the hydrolysis reaction, and 2) stabilization of protein conformation by direct interaction with the peptide backbone and charged side chains. Experiments using IgG4 molecules IgG4 _CDR-Y and IgG4 _CDR-Z with the same CH domains as IgG4 _CDR-X, but different complementarity-determining regions (CDRs), indicate that the stability of the HC C-terminal region is also closely related to the sequence of the CDRs. The stability of IgG4 _CDR-X is significantly improved when binding to its target. Both observations suggest that there are potential interactions between Fab and CH2-CH3 domains, which could be the key factor affecting the stability of IgG antibodies.